Effect Of Toxicity Of Neem (Azadirachta Indica A. Juss) And Mohaneem (Melia Azedarach Linnaeus) On The Larvae Of Mosquito Culex Quinquefasciatus (Say) (Diptera: Culicidae) - Khan, Humayun Reza; Rahman, Jinifath Ir; Tanjina, Taiyeba; Afia, Humayera (Journal of the Asiatic Society of Bangladesh, Science, 2016)
The larvicidal activities of three solvent extracts, viz. ethanol, chloroform and water of two plants neem Azadirachta indica (A. Juss) and mohaneem Melia azedarach (Linn.) against the fourth instar larvae of mosquito Culex quinquefasciatus (Say) (Diptera: Culicidae) were studied in the laboratory at 27 ± 2 °C and 75-85% RH. No larval mortality was observed in control treatment. The larval mortalities by the ethanol extracts of A. indica at the five dose concentrations were 37.33, 64.00, 64.00, 76.00 and 97.33%, respectively; by the chloroform extracts were 24.00, 54.66, 80.00, 96.00 and 100%, respectively; by the water extracts were 32.00, 56.00, 62.66, 68.00 and 81.33%, respectively. The larval mortalities by the ethanol extracts of M. azedarach at the five dose concentrations were 29.33, 58.66, 64.00, 74.66 and 89.33%, respectively; by the chloroform extracts were 40.00, 49.33, 61.33, 73.33 and 84.00%, respectively; by the water extracts were 29.33, 58.66, 64.00, 74.66 and 89.33%, respectively. In case of A. indica, LC50, LC 90 and LC99 values for the ethanol extracts were 1.805, 3.581 and 6.261 mg/ml, respectively; for the chloroform extracts were 0.686, 1.112, and 1.648 mg/ml, respectively; and for the water extracts were 3.002, 5.584 and 9.262 mg/ml, respectively. In case of M. azedarach, LC50, LC 90 and LC99 values for the ethanol extracts were 1.949, 3.89 and 6.835 mg/ml, respectively; for the chloroform extracts were 0.695, 2.256, and 5.886 mg/ml, respectively; and for the water extracts were 3.536, 6.662 and 10.866 mg/ml, respectively. Asiat. Soc. Bangladesh, Sci. 42(2): 209-218, December 2016